2016
DOI: 10.1080/21635781.2016.1181582
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parental Operational Stress Injury on Child Mental Health and Well-Being: A Scoping Review

Abstract: Recognizing the impact of parental mental health on child development, the purpose of this scoping review was to identify and synthesize the research literature describing the impact of parental operational stress injury (OSI) on children and youth from military and veteran families. Arksey and O'Malley's 2005 guidelines for conducting scoping reviews were followed. A total of 18 separate databases were searched, in addition to three university-based discovery platforms. From this search, 506 potential sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 73 publications
(227 reference statements)
1
5
0
Order By: Relevance
“…The results of this study align with Australian and international literature in highlighting the range of impacts of military service, particularly concerning deployment and relocation 38,39 . Specifically, our findings suggested that the majority of parents reported their children were doing well on a range of social and emotional well‐being indicators, demonstrating resilience, sociability and adaptability to the situations they encountered.…”
Section: Discussionsupporting
confidence: 84%
“…The results of this study align with Australian and international literature in highlighting the range of impacts of military service, particularly concerning deployment and relocation 38,39 . Specifically, our findings suggested that the majority of parents reported their children were doing well on a range of social and emotional well‐being indicators, demonstrating resilience, sociability and adaptability to the situations they encountered.…”
Section: Discussionsupporting
confidence: 84%
“…Other populations have evidenced the association of paternal PTSD and adverse child outcomes, including research in Vietnamese child refugees that found a higher risk of mental ill-health associated with paternal PTSD [ 106 ], and research from military families which found impacts of paternal PTSD on negative childhood emotional and behavioural well-being outcomes [ 107 ]. A scoping review identified multiple impacts on the family and children of Canadian military personnel who experienced persistent psychological difficulties as a result of operational duties in the Armed Forces [ 108 ]. Our systematic review found less data with regards to children’s general day-to-day experience of their parent’s ER occupation and parenting.…”
Section: Resultsmentioning
confidence: 99%
“…It is important for occupational therapists in all areas of health care delivery to be sensitive to the potential impact of trauma in their clients’ lives and to adopt a trauma-informed approach to care (Kitchen & Hosegood, 2015; Snedden, 2012). These impacts extend beyond the individuals living with the diagnosis of PTSD to the systems in which they live; increasingly, a family-centred approach to PTSD has been emerging as a priority, recognizing that family systems can promote recovery as well as require support (Cramm, Tam-Seto, Norris, Eichler, & Smith-Evans, 2016; Dekel & Monson, 2010).…”
Section: Discussionmentioning
confidence: 99%